Leveraging gamification to enhance persuasive behaviour and streamline online product returns: an approach grounded in multiple case studies - Panda, Debadrita; Raut, Sachin Kumar; Rana, Sudhir; Shamsudin, Mad Nasir (Emerald Publishing, 2024)
Purpose: The study identifies barriers all stakeholders face in the returns management process. The pressing issue of online product returns significantly erodes the net profit margins, demanding urgent action. Existing returns management systems are often complex, time-consuming and costly, failing to address this issue effectively. In this regard, persuasive technologies like gamification can effectively influence behaviour and enhance motivation towards reducing return by striking a balance between psychological and behavioural factors. Therefore, the study proposes a framework that combines the theory of planned behaviour and Octalysis to identify intentions to reduce product return rates in the e-commerce business. Design/methodology/approach: A qualitative exploratory research design using a multiple case study-based approach with in-depth interviews conducted with 96 varied stakeholders was used to provide insights into the behavioural aspects for reducing return rates in e-commerce. Findings: The results reveal three facets of effective returns management in e-commerce. Customers and delivery partners prioritize return processes, policies and rewards, emphasizing efficiency. Meanwhile, mid- and strategic-level employees are optimistic about return process enhancements. Interdepartmental integration and cross-functional communication are found to be vital, suggesting the need for a gamified framework in returns management. Originality/value: This research enriches the returns management literature on gamification solutions and responds to the need for theoretical anchoring by applying the theory of planned behaviour at the organizational level to improve efficiency and customer centricity in the return process.